Smartphone Usage by College Students and its Impact on Traditional Media - Malik Tariq Mahmood, Muhammad Umar Farooq, Muhammad Shahzad (JSSH, 2024)
The world is on the rise with the advancement of handheld technologies like smartphone which has substituted the traditional media with advanced functions like SMS, telephone, diary, etc. with internet connectivity. College students use smartphon The world is on the rise with the advancement of handheld technologies like smartphone which has substituted the traditional media with advanced functions like SMS, telephone, diary, etc. with internet connectivity.